PENINGKATAN SERAPAN KROMIUM OLEH TANAMAN YANG DIINOKULASI RHIZOBAKTERI - , MMA. Retno Rosariastuti, Ir.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Remediation of chromium contaminated soils is commonly conducted physical and chemical treatments. Both are characterized by environment unfriendly, costly, and rise to secondary impacts. Alternative technique that is cheaper and lead to sustainable is the use of biological agents, termed as bioremediation. The right one in bioremediation is utilization of potential symbiosis between plants (which naturally has ability in adsorption of metal) and rhizobacteria, known as rhizoremediation. The aims of this research were to obtain isolates of rhizobacteria which can increase chromium uptake by plants, studying the effectiveness of the rhizobacteria in increasing chromium uptake by plants, and the mechanisms of chromium hexavalent transformation. Isolation rhizobacteria was conducted by pouring the rhizospheric soils of plants that grow well in chromium contaminated soils in Soil Extract Agar medium, followed by streak plating method to purify the isolates on Luria Bertani medium. Rhizobacteria isolates were selected by bioassay method on Corn plants (Zea maysL.), and identification of the isolates were carried morphologically, physiologically, and molecularly by 16S rDNA sequencing. Study about the effectiveness of Rhizobacteriain increasing chromium uptake by plant was conducted by bioassays on Jute (Boehmerianivea L. Gaud) for getting chromium high accumulation in shoots, and green mustard (Brassica rapa var. Parachinensis L.) for getting chromium high accumulation inroots,cultivated on growing media of sterile Grumusol and Regosol soils supplemented by manure and compost. Observations of this bioassay include dry weight and the content levels of chromium in the roots, and shoots. Study about the mechanism of Cr(VI) transformation was carried out by exposing chromium Cr(VI) to rhizobacteria isolates in the form of growing cells, resting cells, and their supernatant within several hours incubation, then the residual Cr(VI) and the pH value of the medium were measured. These treatment products were applied in bioassays on maize, and then measuring chromium uptake by plants. Isolation resulted 39 rhizobacterial isolates (I1 - I39). Based on the first bioassay on maize, chosen 7 isolates which were influencing chromium absorption by plant, 5 isolates (I26, I30, I37, I38 and I13) inclined to influence chromium accumulation in root and 2 isolates (I3 and I20) in shoot. These 7 isolates were identified and coninued examine. The result of the identification, Isolate I3was identified as genus Rhizobium sp., and isolates I13 , I20 , I26, I30, I37, and I38 were identified as genus Agrobacterium sp. Based on the bioassay on jute, Isolate I3 and combination of isolate I3+compost in grumusol and regosol, efective in increasing plant dry weight and root + shoot chromium uptake (phytostabilization and phytoextraction) 2 times. Based the bioassay on Indian mustard, combination of Isolat I37+manure in grumusol efective in increasing plant dry weight and root, and plant chromium uptake (phytostabilition) 2 times, while ini regosol increasing plant dry weight, root, shoot and plant chromium xix uptake (phytostabilition and phytoextraction) 4 times. Indian mustard as the hyperaccumulator, could be decreased the shoot chromium uptake and increased the root uptake. In the mechanism of Cr(VI) transformation, rhizobacteria produced metabolites especially chromate reductase enzyme and organic acids, which chromate reductase enzyme would reduce Cr(VI) become Cr(III) and organic acids as the electron donor. Keywords: Chromium, Rhizobacteria, Chromium uptake, Jute (Boehmeria nivea L. Gaud), Green Mustard (Brassica rapa var. parachinensis L.).